2006
DOI: 10.1111/j.1748-7692.2006.00031.x
|View full text |Cite
|
Sign up to set email alerts
|

REACTIONS OF CAPTIVE HARBOR PORPOISES (PHOCOENA PHOCOENA) TO PINGER‐LIKE SOUNDS

Abstract: Pingers on gill nets can reduce bycatch of harbor porpoises. If harbor porpoises habituate to pingers, the effect may be reduced or lost. Two captive harbor porpoises were exposed to three sound types. All sounds were in the frequency band from 100 kHz to 140 kHz, 200 ms long, and presented once per 4 s. The source level was 153 dB re 1 Pa RMS at 1 m. Each session consisted of a 10-min presound, a 5-min sound, and a 10-min postsound period. Behavior was recorded on video and on dataloggers placed on the dorsal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 13 publications
0
44
0
Order By: Relevance
“…Conversely, some studies have described an increase in vocalisation by pilot whales during noise exposure (Rendell & Gordon 1999). Two studies also addressed this issue in harbour porpoises: Koschinski et al (2003) found no significant difference in the use of echolocation by porpoises when subjected to turbine noise; Teilmann et al (2006) found echolocation activity of harbour porpoises to decrease in 3 out of 25 sessions when various frequency sounds with a source level of 153 dB re 1 µPa (rms) were played back to them. Although during this study, porpoises in the vicinity of pile driving might have reduced echolocation activity as a response to the sound of pile driving, we see no convincing reason why animals that rely on their sonar for orientation and foraging should cease doing so for over 20 h after pile driving noise stopped.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, some studies have described an increase in vocalisation by pilot whales during noise exposure (Rendell & Gordon 1999). Two studies also addressed this issue in harbour porpoises: Koschinski et al (2003) found no significant difference in the use of echolocation by porpoises when subjected to turbine noise; Teilmann et al (2006) found echolocation activity of harbour porpoises to decrease in 3 out of 25 sessions when various frequency sounds with a source level of 153 dB re 1 µPa (rms) were played back to them. Although during this study, porpoises in the vicinity of pile driving might have reduced echolocation activity as a response to the sound of pile driving, we see no convincing reason why animals that rely on their sonar for orientation and foraging should cease doing so for over 20 h after pile driving noise stopped.…”
Section: Discussionmentioning
confidence: 99%
“…In every case of which we are aware, when a diving animal was stressed, altered ascent and dove deeper, or was unable to access the surface to breathe, the animal maintained the apneic bradycardia or responded with a further decrease in heart rate (Andrews et al, 1997;Dormer et al, 1977;Fedak et al, 1988;Furilla and Jones, 1987;Jobsis et al, 2001;Kvadsheim et al, 2010;Lyamin et al, 2016;Meir et al, 2008;Murdaugh et al, 1961). Despite an increase in body acceleration and prolonged breathholding on exposure to pinger-like sounds, a marked bradycardia also occurred in harbor porpoises (Phocoena phocoena) (Teilmann et al, 2006). In addition, a stressed beluga whale (Delphinapterus leucas), diving with harpoon ECG leads and towing a 1200-pound boat, had a bradycardia of 12 to 24 beats min −1 (King et al, 1953).…”
Section: Discussionmentioning
confidence: 99%
“…, a liberal estimate based on Teilmann et al (2006) and the maximum number of strikes allowed for each track was 15.…”
Section: à2mentioning
confidence: 99%